Influence of Tool Pin Profile and Welding Parameter on Tensile Strength of Magnesium Alloy AZ91 During FSW. (2016) - Patel, Nikul; Bhatt, K.D.; Mehta, Vishal
Abstract: Magnesium is flammable material and to avoid its limitation of fusion welding solid state welding process, called friction stir welding (FSW), is applied for joining two plates together. The friction stir welding uses a non-consumable tool for joining abutting plates of magnesium alloy AZ91 having 6 mm thickness. FSW process joins the plates with advantages such as low distortion, no shielding gas required, and fine recrystallized microstructure. In Friction stir welding, process parameters such as welding speed, tool rotation speed, tool dimensions and axial force play an important role during welding. In the present work, the 6 mm thick plates of the said alloy are joined at welding speed of 28 mm/min to 56 mm/min with tool rotation speed ranging from 710 rpm to 1400 rpm. Tensile testing was carried out to know the best parameter from the selected ones. Observations are also made for any defects by using fluorescent penetrant testing and photo micrographs.